A Novel Hysteresis Current Control Strategy with Fuzzy Bandwidth for Active Power Filter - Liu, Xinyang; Wang, Jie; Yao, Gang (Elektronika ir Elektrotechnika, 2012)
This paper presents a novel hysteresis current control strategy with fuzzy bandwidth for Active Power Filter. Based on the structure of traditional hysteresis current unit of APF and with the analysis of the variation of hysteresis bandwidth, an internal fuzzy controller is designed in order to dynamically adjust the loop width of hysteresis comparator device. Compared to traditional hysteresis method, progresses are made not only in limiting the switching frequency of power switches so that protect the APF device, but also in achieving a more excellent dynamic response and precision of compensation. Finally, the harmonic compensating efficiency to the typical non-linear loads of the approach presented is further verified by the simulation and experiment results in this paper. Ill. 10, bibl. 11, tabl. 1 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.120.4.1442